2013
DOI: 10.1097/pai.0b013e31826e4e61
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Noninvasive Versus Invasive Techniques for the Diagnosis of Helicobacter pylori Infection

Abstract: Among the noninvasive methods for diagnosis of H. pylori infection, the 3 methods used in this study recorded promising results, including good sensitivity, which was the highest in the serum antibody test, whereas the stool-PCR test recorded excellent specificity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
(28 reference statements)
2
1
0
Order By: Relevance
“…They concluded that IgG antibody to H. pylori might be useful in epidemiologic studies involving large numbers of participants. In agreement with the present study, Alam El-Din et al, [ 21 ] concluded that diagnosis of H. pylori infection by noninvasive methods, including the serum antibody test, revealed a sensitivity and positive predictive value of 88.9% and 94.2%, respectively.…”
Section: Discussionsupporting
confidence: 92%
“…They concluded that IgG antibody to H. pylori might be useful in epidemiologic studies involving large numbers of participants. In agreement with the present study, Alam El-Din et al, [ 21 ] concluded that diagnosis of H. pylori infection by noninvasive methods, including the serum antibody test, revealed a sensitivity and positive predictive value of 88.9% and 94.2%, respectively.…”
Section: Discussionsupporting
confidence: 92%
“…Our results are also in disagreement with some results obtained even in different areas of the world, by immunocromatographic assay (4,9,18) . On the other hand, our results are similar to results achieved in Egypt (1,5) . Egypt has a high prevalence of H. pylori infection.…”
Section: Discussionsupporting
confidence: 81%
“…These tests do not need endoscopy and biopsy. Due to the character invasive of endoscopy and biopsy, there is a growing interest in the use of non-invasive methods (1) . Among the non-invasive methods, urea breath test is the most reliable due to its high sensitivity and specificity.…”
Section: Introductionmentioning
confidence: 99%